The Effectiveness of Virtual Reality Application for Women Undergoing Episiotomy Repair: A Systematic Review and Meta-analysis - Elham Manouchehri; Somayeh Makvandi; Zahra Hadizadeh Talasaz; Elham Azmoude; Mona Larki (Journal of Caring Sciences)
Introduction: Virtual reality (VR) is effective in several healthcare domains. As of date, there have been no systematic reviews investigating the efficacy of VR technology in episiotomy repair in women. This systematic review and meta-analysis examined the effects of using VR on pain, anxiety and satisfaction in women under episiotomy repair. Methods: For the original articles, six databases were searched using relevant keywords without restriction on time or languages until June 6, 2024. The Cochrane risk-of-bias tool for randomized trials (RoB) and the Risk of Bias Assessment Tool for Nonrandomized Studies (RoBANS) were both used to assess the risk of bias in randomized and non-randomized studies, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) also determined the quality of our evidence. All analyses employed Comprehensive Meta-Analysis (CMA) V.2. Results: Five randomized clinical trial and two quasi-experimental studies with poor-to high-quality met the inclusion criteria. The VR significantly decreased perineal pain during [MD (95% CI)=-1.622 (-2.598, -0.645), P=0.001], immediately after [MD (95% CI)=-1.931 (-2.785, -1.076), P<0.001], and one hour after [MD (95% CI)=-1.596 (-2.436, -0.765), P<0.001]. It also significantly decreased anxiety [SMD (95% CI)=-1.48 (-2.451, -0.509), P=0.003] after repair. VR group participants were significantly more satisfied than the control group. The quality of was moderate for perineal pain intensity one hour after episiotomy repair and anxiety after episiotomy repair. Conclusion: Given the efficacy of VR on pain, anxiety, and satisfaction, it is suggested that it be utilized as a novel modality to enhance the quality of maternity hospital care.